Revisiting the Systematic Method of Bruce Archer: A Review on Design as the Third Culture - Song, Yi; Wang, Min (The Design journal, 2025)
In pursuing a systematic method to address design problems, Bruce Archer developed the concept of design as 'the third culture'. Due to the setbacks experienced in the exploration of design methodology in the 1960s, Archer began to advocate for a more adaptive and integrative method, shifting from the rigid application of scientific methods to a more flexible understanding of design problems. This transformation greatly influenced contemporary design thinking. This study re-evaluates the three characteristics of Archer's systematic method: 'creative thinking', 'the balance between design & science', and 'the nonlinear design method/feedback'. Archer's proposition of design as 'the third culture' aims to bridge the gap between science and the humanities, encouraging creative thinking and co-design to address complex design problems, fostering the integration of knowledge across disciplines and enhancing the ability to tackle the multifaceted challenges of socio-ecological systems.